Analisis Tindak Tutur Lokusi pada Podcast Kemal Palevi dengan Habib Ja’far Episode “Penuh Ilmu Kehidupan” (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The method used in this analysis is descriptive qualitative. Data were collected by watching Kemal Palevi’s podcast video and taking notes on important points in line with the analysis. The results of this analysis show that Kemal Pahlevi frequently uses locutioary speech acts in his content. Locutionary speech acst are speech acts delivered to state something. This research produced findings in the form of declarative and interrogative locutionaryspeech acts. The benefit of this reseach is to enrich knowledge in the field of pragmatics, particulary regarding locutionary speech acts.